Implementasi Asistensi Mengajar Melalui Pembelajaran Team Games Tournament Di SMAN 2 Lalan - Sumarni, Siti; Sari, Ayu Puspita Indah (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
The purpose of this study is to see whether students learn better by using Classroom Action Research consisting of a Team Games Tournament learning model based on Problem Mine with action research steps starting from planning, implementation and evaluation. In this study, students were given the opportunity to learn by developing themselves outside the campus through Teaching Assistance in Education units. The method of implementing observation activities, this method was chosen because the researcher saw the object under study directly. During the implementation of teaching assistance activities at SMA Negeri 2 LALAN, assistance students have participated in various programs at SMA Negeri 2 LALAN both academic, non-academic, formal, and non-formal. The result of this study is that researchers can find out the learning outcomes of students after using the Team Games Tournament learning media based on Mine Problem.